The effect of intermittent cryotherapy on the activities of citrate synthase and lactate dehydrogenase in regenerating skeletal muscle - Oliveira, Nuno Miguel Lopes de (2013)
This study examined the effect of three sessions of cryotherapy (three sessions of 30 minutes applied each 2 h) and muscle compression in the regenerating skeletal muscle of the rats. The middle belly of tibialis anterior muscle was injured by a frozen iron bar and received one of the following intervention: injury + cryotherapy (treated with cryotherapy); injury + placebo (sand pack), and injury (I).The enzymatic activities of citrate synthase (CS) and lactate dehydrogenase (LDH) were measured in the presence of 1mM or 10mM pyruvate. The ANOVA and Tukey’s test (p£0.05) were performed for the statistical analysis. In summary, the intermittent sessions of cryotherapy, associated to muscle compression and applied immediately after the primary muscle injury minimized the CS and LDH activity at 4h30 and 24h periods post-lesion, which could be related to the reduction in the secondary muscle injury inherent to cryotherapy treatment.